1997
DOI: 10.1007/s11746-997-0185-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of high‐melting palm stearin in lipase‐catalyzed interesterification with liquid oils

Abstract: Palm stearin with a melting point (m.p.) of 49.8°C was fractionated from acetone to produce a low-melting palm stearin (m.p. = 35°C) and a higher-melting palm stearin (HMPS, m.p. = 58°C) fraction. HMPS was modified by interesterification with 60% (by weight) of individual liquid oils from sunflower, soybean, and rice bran by means of Mucor miehei lipase. The interesterified products were evaluated for m.p., solid fat content, and carbon number glyceride composition. When HMPS was interesterified individually w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
1
16
2
2
Order By: Relevance
“…Increases in SMP that occurred after interesterification may be attributed to the increase of CN 48 (trisaturated) TAG. The results are in contrast with Ghosh and Bhattacharyya [17] who found that the enzymatic interesterification of high-melting point palm stearin with liquid oils resulted in a decrease of the melting point of non-interesterified blends. All the interesterified blends had SMP lower than 40 7C, so they met the ISIRI specifications.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Increases in SMP that occurred after interesterification may be attributed to the increase of CN 48 (trisaturated) TAG. The results are in contrast with Ghosh and Bhattacharyya [17] who found that the enzymatic interesterification of high-melting point palm stearin with liquid oils resulted in a decrease of the melting point of non-interesterified blends. All the interesterified blends had SMP lower than 40 7C, so they met the ISIRI specifications.…”
Section: Resultscontrasting
confidence: 99%
“…2, as the portion of POL increases, a decrease in IV is observed. This is due to the increase in the amount of SFA and the decrease in unsaturated fatty [17] reported that interesterification of binary blends of high-melting point palm stearin with sunflower, soybean and rice bran oil with 10% Mocur miehi lipase at 60 7C for 5 h causes a decrease in CN 48 and CN 54 TAG and an increase in CN 50 and CN 52 TAG of the blends, which is different from the changes observed in the blends studied in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…The product contained polyunsaturated fatty acids and was virtually free of trans acids. 111 When lard and high-oleic sun¯ower (60:40) were interesteri®ed (Candida antarctica, 55°C, 24 h) the product was superior to that obtained by blending alone and had solid content resembling that of a soft margarine at a range of temperatures. 112 From the examination of a ternary mixture of canola oil, hydrogenated canola oil, and palm stearin Cho and deMan 113 concluded that the interesteri®cation product crystallised in the desirable b' form and could be used to produce margarine with trans levels lower than conventional products made from hydrogenated oils even though trans acids were still present.…”
Section: (Iii) Margarine and Shorteningmentioning
confidence: 96%
“…To overcome this problem, interesterification can be used to produce a fat with a gradual melting profile. In this process, a blend of lipids high in saturated (e.g., tropical or 100% hydrogenated fats) and unsaturated FAs is mixed with a catalyst such as sodium methoxide (23) or various lipase sources (24). This process initially produces a diacylglycerol anion (2).…”
Section: Solid Fats For Use In Foodsmentioning
confidence: 99%